2022
DOI: 10.1007/s10904-022-02325-w
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanoarchitectonics of Antimicrobial Tiles and a Quest for Anti-SARS-CoV-2 Tiles

Abstract: Design of antimicrobial tiles seems necessary to combat against contagious diseases, especially COVID-19. In addition to personal hygiene, this technology facilitates public hygiene as antimicrobial tiles can be installed at hospitals, schools, banks, offices, lobbies, railway stations, etc. This review is primarily focused on preparing antimicrobial tiles using an antimicrobial layer or coatings that fight against germs. The salient features and working mechanisms of antimicrobial tiles are highlighted. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…These features make it easier for bacteria to be attracted to nanosilica, resulting in improved bacterial acid resistance. In addition, studies [69,83,84] have shown that the presence of silicon dioxide particles in the medium leads to an upsurge in the negative surface charge possessed by some gram-negative bacteria. The charge density elevation is induced by a change in porin conformation caused by particle adsorption onto cell surfaces.…”
Section: Major Nanoparticles Used In Agriculturementioning
confidence: 99%
“…These features make it easier for bacteria to be attracted to nanosilica, resulting in improved bacterial acid resistance. In addition, studies [69,83,84] have shown that the presence of silicon dioxide particles in the medium leads to an upsurge in the negative surface charge possessed by some gram-negative bacteria. The charge density elevation is induced by a change in porin conformation caused by particle adsorption onto cell surfaces.…”
Section: Major Nanoparticles Used In Agriculturementioning
confidence: 99%
“…The use of such samples as footpath tiles in Bangladesh is an alternative to the traditional ceramic tiles available on the market. On the other hand, the problem associated with an increased amount of plastic waste during COVID-19 could be a solution to getting rid of plastic waste [5].…”
Section: Introductionmentioning
confidence: 99%